Resource abundance of cobalt-rich ferromanganese crusts in the KC-8 seamount, West Pacific - Hwang, Gyuha; Ko, Youngtak; Yang, Seungjin; Kim, Wonnyon (Frontiers in Earth Science, 2024)
We have estimated the resource potential of cobalt-rich ferromanganese crusts (CFCs) on the summit area of the KC-8 seamount in the West Pacific, based on the acoustic backscatter intensity (ABI), ROV video footage, and CFC thickness measurements. To estimate the spatial distribution of CFC across 13 equally divided blocks within a 360 km2 area, shipboard and deep-tow ABIs were compared with visual data. The presence of CFCs is evident in the areas where ABI is higher than average, validating the use of ABI data to delineate the exposure of CFCs. With high accuracy in distinguishing between CFCs and sediment-dominant areas, the distribution area of CFCs was precisely calculated. The variation in CFC thickness across the KC-8 seamount summit was measured through CFC samples retrieved using a CFC corer. CFC thickness is highly variable even between adjacent sites, but it shows a roughly increasing trend from south to northwest. Based on the CFC distribution area associated with thickness, we calculated a CFC resource abundance. Of the estimation, 82% have remained on the gentle slope (<10°) areas, which can be accessible for future mining. Overall, our study suggests that the combination of an acoustic survey with reliable thickness information is highly effective in estimating CFC abundance.